2017
DOI: 10.5811/cpcem.2017.3.33369
|View full text |Cite
|
Sign up to set email alerts
|

Hematometrocolpos in a Pubescent Girl with Abdominal Pain

Abstract: Hematometrocolpos is a rare congenital abnormality of the female urogenital system that leads to an imperforate hymen and subsequent retrograde menstruation. We present the case of a 14-year-old female patient who presented to the emergency department with amenorrhea and abdominal pain, and was found to have an imperforate hymen and hematometrocolpos on trans-abdominal point-of-care ultrasound. It is important for emergency physicians to consider this diagnosis in pubescent female patients presenting with abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Cases are typically diagnosed after menarche due to symptoms manifesting as a result of the retrograde accumulation of blood in the vagina and uterus during menstruation [ 3 , 4 ]. The imperforate hymen may manifest with retained blood within the uterus (hematometria), vagina (hematocolpos), or both (hematometrocolpos) [ 5 ]. Diagnosis of hematometrocolpos can be made with ultrasonography revealing hypoechoic material within a distended uterus and vaginal canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases are typically diagnosed after menarche due to symptoms manifesting as a result of the retrograde accumulation of blood in the vagina and uterus during menstruation [ 3 , 4 ]. The imperforate hymen may manifest with retained blood within the uterus (hematometria), vagina (hematocolpos), or both (hematometrocolpos) [ 5 ]. Diagnosis of hematometrocolpos can be made with ultrasonography revealing hypoechoic material within a distended uterus and vaginal canal.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially helpful as the initial symptoms may be present in a wide range of pathologies, and the proper utilization of bedside ultrasonography may help to rapidly and accurately narrow the differential diagnosis. Treatment is based on identifying and treating the underlying imperforate hymen with surgical approaches and subsequent drainage of the hematometrocolpos [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this instant case, even a cursory exam would have revealed that the problem was an imperforate hymen which would present as a bulging, protruding, bluish membrane that allows positive transillumination at the introitus. [14] This observation would also have resulted in a more appropriate referral and early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Given that normal menses typically include 30 to 80 mL of blood and frequently 900 mL of blood or more are evacuated at the time of surgery menarche could have been on-going for many months before presentation. [16][17][18] The average age of menarche in the United States is age 12 in white girls and 11 in black and Hispanic girls, but can be as early as 9 to 10 years of age. In a systematic review of imperforate hymen, the majority of patients (65%) presented between age 12 and 18, compared with 14% between ages 2 and 12.…”
Section: Prepubertalmentioning
confidence: 99%
“…They typically present within 3 to 6 months from the onset of menstruation. Given that normal menses typically include 30 to 80 mL of blood and frequently 900 mL of blood or more are evacuated at the time of surgery menarche could have been on-going for many months before presentation 16–18…”
Section: Introductionmentioning
confidence: 99%